2021
DOI: 10.4038/sljch.v50i4.9851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parental emotion regulation ability and parent-child attachment on adolescent’s emotion regulation ability in Colombo, Sri Lanka

Abstract: Introduction: Many global studies identify the importance of parental emotion regulation (ER) and quality of parent-child attachment on children's ER ability. Such research is rare in Sri Lanka.Objective: To assess the association between parental ER difficulties, quality of parent child attachment and temperament on adolescents' ER difficulties.Method: A cross sectional study was done on 233, 12-14 year old adolescents and 349 parents accessed from a Type AB, Type C and Type 2 school and from a Christian and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…While Silva et al (2018) found no association between the paternal use of modelling of cognitive strategies and ER in adolescents, such an association was found in two other studies (Cheung et al, 2020; Gunawardena & Schuck, 2021). These findings corroborate the previous evidence reporting that maternal modelling of emotion dysregulation was significantly associated with adolescents' ER difficulties (Morelen et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…While Silva et al (2018) found no association between the paternal use of modelling of cognitive strategies and ER in adolescents, such an association was found in two other studies (Cheung et al, 2020; Gunawardena & Schuck, 2021). These findings corroborate the previous evidence reporting that maternal modelling of emotion dysregulation was significantly associated with adolescents' ER difficulties (Morelen et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…Four of five studies found that the quality of the father–infant attachment was significantly associated with a child's ER (Boldt et al, 2020; Diener et al, 2002; Fernandes et al, 2021; Gunawardena & Schuck, 2021). Of these, three studies examined fathers' attachment in infancy (Diener et al, 2002; Fernandes et al, 2021) and preschool (Boldt et al, 2020), while one study was conducted with adolescent samples (Gunawardena & Schuck, 2021). Volling's (2001) study reported no association between a child's attachment to their father assessed at 12 months and ER strategies in 4‐year‐old children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pandemic’s impact on children’s mental health and parental stress in Sri Lanka is only anecdotal; no studies have explored psychological wellbeing during this period so far. Moreover, during the pandemic and even in pre-pandemic times, children’s psychological well-being on parent stress and vice versa had hardly been explored in the Sri Lankan context [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%